Within the changing geometry of European integration processes (Economic and Political Thought, 2015)
The concepts of differentiated integration in the EU emerged as a resultof increasing diversification defined in terms of an economic developmentlevel, cultural heritage and nations’ political and social preferences. The principleof flexibility, which was applied to establish the countries of the ‘hardcore’, allows the EU Member States to implement their enhanced cooperation.Therefore, the principle is considered to be the main ‘instrument’ for‘differentiated integration’. The idea of a ‘two-speed’ Europe creates anothercategory of the EU Member States, which should be supported economicallyin order to prevent the ‘hard core’ countries from strengthening.